Quantitative IVIM parameters evaluating perfusion changes in brain parenchyma in patients newly diagnosed with acute leukemia: Compared with healthy participants - Cui, Jianing; Zheng, Jing; Niu, Weiran; Bian, Wenjin; Wang, Jun; Niu, Jinliang (Frontiers in Neurology, 2023)
Purpose To study the value of quantitative IVIM parameters in evaluating cerebral blood perfusion changes in patients newly diagnosed with acute leukemia (AL) by comparing them with healthy participants. Materials and methods This prospective study consecutively recruited 49 participants with newly diagnosed AL and 40 normal controls between July 2020 and September 2022. All participants underwent an MRI of the brain using an axial T1-weighted and an IVIM sequence. The IVIM parameters (water diffusion coefficient, sADC, pseudoperfusion fraction, f; diffusion coefficient, D, pseudodiffusion coefficient, D*, and perfusion-diffusion ratio, PDR) and peripheral white blood cell (WBC) counts were obtained. An unpaired t-test or the Mann–Whitney U-test was performed to compare the differences in gray matter (GM) and white matter (WM) of healthy participants and AL patients and the differences in IVIM parameters between healthy participants and patients with AL. In addition, multivariate (logistic regression) analyses were used to identify independent predictors and then, the receiver operating characteristic curve (ROC) analyses were performed. Results 40 healthy participants and 49 patients with newly diagnosed AL were evaluated. In healthy participants, sADC, PDR, D and f values of GM were significantly higher than those of WM (t = 5.844, t = 3.838, t = 7.711, z = −2.184, respectively, all P < 0.05). In AL patients, the D, f and sADC values of GM were significantly higher than those of WM (t = 3.450, t = 6.262, t = 4.053, respectively, all P < 0.05). The sADC and f value from AL patients were significantly lower than those from healthy participants in GM (z = −2.537, P = 0.011; and z = −2.583, P = 0.010, respectively) and WM (z = −2.969, P = 0.003; z = −2.923, P = 0.003, respectively). The WBC counts of AL patients were significantly higher than those of healthy participants (t = 3.147, P = 0.002). Multivariate analyses showed that the f values of GM and WM were independent predictors of AL (P = 0.030, and 0.010, respectively), with the optimal cut-off value at 7.08% (AUC ROC curve: 0.661, specificity: 11.4%, sensitivity: 98%) and 13.77% (AUC ROC curve: 0.682, specificity: 79.5%, sensitivity: 59.2%). Conclusion The IVIM parameters of brain parenchyma in patients newly diagnosed with AL differed from those of the healthy participants. The changes of cerebral blood flow perfusion are expected to provide new ideas for studying central nervous system infiltration in AL.